EXPLORING THE BENEFITS OF MULTIMODAL LITERACY IN ENGLISH TEACHING: ENGAGING STUDENTS THROUGH VISUAL, AUDITORY, AND DIGITAL MODES - Sutrisno, Djoko; Noor Azlinda Zainal Abidin; Nanda Pambudi; Aydawati, Emilia; Sulfikar Sallu (Global Synthesis in Education Journal, 2023)
This research paper investigates the benefits of integrating multimodal literacy into English teaching practices. Multimodal literacy refers to the ability to comprehend and create meaning using multiple modes of communication, such as visuals, auditory elements, and digital technologies. The study aims to explore how incorporating multimodal approaches can enhance student engagement and learning outcomes in English classrooms. Drawing on recent research and educational theories, this paper examines the theoretical underpinnings of multimodal literacy and its potential impact on language acquisition. The research employs a qualitative approach, including classroom observations, interviews, and student feedback, to gather data and provide insights into the effectiveness of multimodal literacy strategies. The findings contribute to the understanding of innovative teaching practices that promote student engagement, critical thinking, and communication skills in English language learning contexts.